2015
DOI: 10.1519/jsc.0000000000000780
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Whole-Body Vibration, Light-Emitting Diode, and Cycling Warm-up on High-Intensity Physical Performance During Sprint Bicycle Exercise

Abstract: The purpose of this study was to compare the effects of light-emitting diode (LED) irradiation and whole-body vibration (WBV) delivered either in isolation or combination (LED + WBV), warm-up (WU), and a control (C) treatment on performance during a sprint bicycle exercise. Ten cyclists performed a 30-second sprint cycle test under these conditions. The LED light was applied at 4 points bilaterally. Whole-body vibration consisted of 5 minutes of squats associated with WBV. LED + WBV consisted of WBV followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Studies that have examined the effects of PBMT on recovery and performance following exercise protocols include simple open-chain isolated single-joint exercises, such as knee extension (Antonialli et al, 2014;Baroni et al, 2015;de Paiva et al, 2016;Rossato et al, 2018) and elbow flexion (Larkin-Kaiser et al, 2015;Machado et al, 2017;Nausheen et al, 2017;Rigby and Hagan, 2019;Vieira et al, 2019). Studies have progressed to more dynamic protocols, such as such as in-game competitions (De Marchi et al, 2019;Dornelles et al, 2019), sport-specific tests (Pinto et al, 2016), running (Malta et al, 2016(Malta et al, , 2018Dellagrana et al, 2018;Peserico et al, 2019), plyometrics (Fritsch et al, 2016), and cycling (Teles et al, 2015;Malta et al, 2018). In addition, research has examined highly-trained sample populations, such as athletes in jiu-jitsu (Follmer et al, 2018), judo (Orssatto et al, 2019), volleyball (Ferraresi et al, 2015;da Cunha et al, 2019;Vieira et al, 2019), rugby (Pinto et al, 2016), water polo (Zagatto et al, 2016), and futsal (De Marchi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that have examined the effects of PBMT on recovery and performance following exercise protocols include simple open-chain isolated single-joint exercises, such as knee extension (Antonialli et al, 2014;Baroni et al, 2015;de Paiva et al, 2016;Rossato et al, 2018) and elbow flexion (Larkin-Kaiser et al, 2015;Machado et al, 2017;Nausheen et al, 2017;Rigby and Hagan, 2019;Vieira et al, 2019). Studies have progressed to more dynamic protocols, such as such as in-game competitions (De Marchi et al, 2019;Dornelles et al, 2019), sport-specific tests (Pinto et al, 2016), running (Malta et al, 2016(Malta et al, , 2018Dellagrana et al, 2018;Peserico et al, 2019), plyometrics (Fritsch et al, 2016), and cycling (Teles et al, 2015;Malta et al, 2018). In addition, research has examined highly-trained sample populations, such as athletes in jiu-jitsu (Follmer et al, 2018), judo (Orssatto et al, 2019), volleyball (Ferraresi et al, 2015;da Cunha et al, 2019;Vieira et al, 2019), rugby (Pinto et al, 2016), water polo (Zagatto et al, 2016), and futsal (De Marchi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the conventional method of instrumentation is the use of a handheld device to treat localized muscle tissue (Teles et al, 2015;Pinto et al, 2016;Miranda et al, 2018;Vieira et al, 2019). As expected, larger devices, such as whole-body light beds (Zhao et al, 2012), have minimal research due to their cost (∼$60,000-$130,000) but are assumed to be advantageous by treating more target tissue in a shorter amount of time.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also did not perform a warm-up or familiarization with the procedures (32). Another study, including a larger area of irradiation, covering the main muscles used in the Wingate test, also did not find any ergogenic effects after phototherapy (42). The authors observed that an active warm-up, including sprinting, was able to improve peak and relative power, and total work compared with other ergogenic methods applied in isolation (42).…”
Section: Introductionmentioning
confidence: 99%
“…Because of its characteristics, the Wingate test can be used to evaluate the effects of ergogenic resources on anaerobic capacity (17,21,26,36). Two studies evaluated the effects of photobiomodulation when applied before the Wingate test (32,42). In 1 study, volleyball and soccer athletes performed a Wingate test after applying phototherapy to the quadriceps muscles, and the authors found no effects on total work performed (32).…”
Section: Introductionmentioning
confidence: 99%
“…The Whole-body vibration exercise (WBVE) has received plenty of attention for its ability for improving strength and power in the lower-body (Cormie et al, 2006;Avelar et al, 2012;Teles et al, 2015), whereas only a few studies investigated the effects of the vibratory stimulus on upper-body to date (Cochrane and Hawke, 2007;Marín et al, 2010Marín et al, , 2013Jones et al, 2017). In the clinical and rehabilitation scenario, handgrip strength (HS) can be used for clinical-functional assessment and diagnosis, evolution and progression of the treatment (Shiratori et al, 2014).…”
Section: Introductionmentioning
confidence: 99%